2021
DOI: 10.1186/s12885-021-08880-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementing supportive exercise interventions in the colorectal cancer care pathway: a process evaluation of the PREPARE-ABC randomised controlled trial

Abstract: Background A colorectal resection is standard treatment for patients with colorectal cancer (CRC). However, the procedure results in significant post-operative mortality and reduced quality of life. Maximising pre-operative cardiopulmonary fitness could improve post-surgical outcomes. PREPARE-ABC is a multi-centre, three-armed, randomised controlled trial investigating the effects of exercise interventions, with motivational support on short and longer-term recovery outcomes in CRC patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Success was mainly due to the visionary leadership and a diverse and committed group of interdisciplinary stakeholders working together to adapt and refine a tailored stepped-care MCPP for local implementation at a Cancer Unit in Northern Ireland [ 14 ]. Current research investigating the feasibility and acceptability of MCPPs from the perspectives of professionals and patients is exceptionally limited [ 17 ] with studies often referring to patient recruitment and participation as indicators of success [ 22 , 23 ]. The findings from this study extend current evidence by illustrating the mechanisms of success and challenges experienced by those at SET and will be discussed through the lens of NPT components [ 20 ], coherence, cognitive participation, collective action and reflexive monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success was mainly due to the visionary leadership and a diverse and committed group of interdisciplinary stakeholders working together to adapt and refine a tailored stepped-care MCPP for local implementation at a Cancer Unit in Northern Ireland [ 14 ]. Current research investigating the feasibility and acceptability of MCPPs from the perspectives of professionals and patients is exceptionally limited [ 17 ] with studies often referring to patient recruitment and participation as indicators of success [ 22 , 23 ]. The findings from this study extend current evidence by illustrating the mechanisms of success and challenges experienced by those at SET and will be discussed through the lens of NPT components [ 20 ], coherence, cognitive participation, collective action and reflexive monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This would enable an enhanced understanding of processes and mechanisms leading to MCPP’s success and failure, paramount prior to scaling up and further roll-out [ 16 ]. To date, the authors are aware of only one MCPP qualitative feasibility study, however the focus was solely upon delivery fidelity and acceptability [ 17 ]. This novel paper aims to explore mechanisms promoting feasibility and acceptability of a MCPP from patients’ and professionals’ perspectives exploring planning, development and implementation phases.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we did not collect comparative data from people who did not receive support from an AP. A randomized pragmatic study should therefore be carried out in a real setting [ 41 ] to better capture the effect of APs in healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Success was mainly due to the visionary leadership and diverse and committed group of interdisciplinary professionals working together to adapt and refine a tailored stepped-care MCPP for local implementation at a Cancer Unit in Northern Ireland [14]. Current research investigating the feasibility and acceptability of MCPPs from the perspectives of professionals and patients is exceptionally limited [17] with studies often referring to patient recruitment and participation as indicators of success [23][24]. The findings from this study extend current evidence by illustrating the mechanisms of success and challenges experienced by those at SET and will be discussed through the lens of NPT components [20], coherence, cognitive participation, collective action and reflexive monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of the SET MCPP exercise component was critiqued by some HPs at a strategic level as requiring more specific and intensive exercise prescription, despite the agreed exercise doses outlined in the MCPP Standard Operating Procedure manual. Murdoch et al [17] study of their MCPP with a CRC patient group suggested that while professionals emphasised that fitness was important for surgery outcomes, patients were not encouraged to increase activity levels. Herein, they noted that the lack of exercise prescription was attributed to a short timeframe between diagnosis and treatment, plus constrained resources with clinicians being too busy [17].…”
Section: Discussionmentioning
confidence: 99%